Avaliação da infiltração microbiana na interface implante-abutment em conexões tipo hexágono interno e cone-morse de implantes osseointegráveis - SANTANA, Washington Macedo de (2007)
The scientific literature has reported that dental implants can be affected by the oral microorganisms through the formation of a bacterial biofilm. The region most affected is the connection between the implant platform and the prosthetic abutment, particularly in implants with an external connection. Therefore, the region of the implant/abutment connection can participate in the development of peri-mucositis or peri-implantitis. They propose that these implant/abutment connections known as morse taper provide an effective seal against microorganisms. Thus the objective of this research was to evaluate the microleakage on the implant/abutment interface of internal hex and morse taper prosthetic connections. Thirty five (35) implants were selected and divided into seven (7) groups (5 groups of implants from Brazilian manufacturers and 2 groups of implants manufactured abroad). The tested implants were Straumann (Straumann AG® / Switzerland), Ankylos (Dentsply-Friadent® / Germany), AR Morse (Conexão/Sistema de Prótese® São Paulo-SP), Titamax CM (Neodent® /Curitiba-PR), Titamax II Plus (Neodent®/Curitiba-PR), Stronger (Sin/Sistema Nacional de Implante® São Paulo - SP) e Titanium Fix CM (AS Technology / São José dos Campos-SP). For the microbiological test the bacterium Enterococus faecalis (ATCC 29212) was selected. This bacterium was inoculated in the interior aspect of the implant followed by immediate installation and final torque (N/cm) of the prosthetic abutment. The implant/abutment set up was then placed in a Brain Heart Infusion broth (BHI) and incubated in this broth for 14 days. During this period, the cloudiness of the broth was evaluated at days 7 and 14. The data were statistically analyzed by the Kruskal Wallis method. The results demonstrated that all samples from both Ankylos and Neodent CM groups did not present microleakage. Although 20% of samples from Conexao AR Morse group presented microleakage, there was no significant statistical difference when compared to the former two groups. Furthermore, all samples from Straumann,Titanium Fix CM, Neodent Titamax II Plus, and SIN Strong groups presented microleakage after 14 days of culture (p=0.05), though correlation analysis among these samples did not reveal significant statistical differences.